To solve the equation \((x + 3)^2 = 36\) using square roots, follow these steps:
-
Take the square root of both sides: \[ x + 3 = \pm 6 \] This means we have two cases to consider: \[ x + 3 = 6 \quad \text{and} \quad x + 3 = -6 \]
-
Solve each case separately:
-
First case: \(x + 3 = 6\) \[ x = 6 - 3 = 3 \]
-
Second case: \(x + 3 = -6\) \[ x = -6 - 3 = -9 \]
-
-
Write the solutions: The solutions to the equation \((x + 3)^2 = 36\) are: \[ x = 3 \quad \text{and} \quad x = -9 \]
Thus, the final answer is: \[ x = 3 \quad \text{and} \quad x = -9 \]